Jawabanmu

2014-02-06T20:39:06+07:00
F (x+1) =  x^{2} + 3x + 3
         =  (x+1)^{2} + 3(x+1) + 3
         =  x^{2} + 2x +1 + 3x + 3 + 3
         =  x^{2} + 5x + 4
a . f(x) =  x^{2} + 5x + 4
b . f (-1) =  (-1)^{2} + 5(-1) + 4
           = 1 + (-5) + 4
           = 0

kalo f(x) nya gimana?
kalo gak salah ya .. :) maaf kalo salah
iya makasih ya, gpp kok :)
2014-02-06T20:48:34+07:00
A) f(x+1) = x^2 +3x+3
    f(x-1) = f(x) = (x-1)^2 +3(x-1) + 3
                    = x^2 - 2x + 1 + 3x - 3 + 3
                    = x^2 + x + 1
b) f(-1) = (-1)^2 +(-1) +1 =1-1+1= 1

:D